STREET SOCIAL WORK WITH YOUTH – THE FIRST EXPERIENCES IN LITHUANIA - ŠVEDAITĖ-SAKALAUSKĖ, Birutė; EIDUKEVIČIŪTĖ, Danielė (Socialinė teorija, empirija, politika ir praktika, 2015)
This article represents the theoretical concept of social work with youth on the street (as well as the mobile youth work), which already exists in the world for over 40 years. The first experiences of social street work in Lithuania are also discussed by using data from qualitative research. The article focuses on the public reasons of the occurrence strategy and analyses the principle posture of social work on the street, discusses directions, goals and functions of working on the street, looks into the methodology, and needed competencies for street social workers. The article highlights the main problems, critical points and specific challenges of street social work in Lithuania. All in all, the conception of street social work with youth has arrived into the country. Despite the fact that there are just a few organisations which have limited resources (human, material, power and influence sense) that are trying to develop and implement the street social work in Lithuania and the fact that the Lithuanian social policy hasn’t recognised the need for street social work with youth yet, we can say that the start has been made. The first projects of street social work in our country are entirely consistent with the substantive provisions of both paradigmatic posture and its methodology. That is why they can be recognised as the same phenomenon as in the West, which is known as Street social work.